Commercializing technological research and skills: drivers from European technology institutes. Issue 3 (2nd July 2016) - Vivas, Carlos
Abstract : Europe, a world-player in research and technology development, is lacking the ability to turn scientific research and skills into economic and social wealth through innovation. Technology Institutes (TIs) are potential catalysts and exist as an interface between science and industry. TIs have a potentially powerful influence over economic and technological development through their contributions to industrial innovation. Therefore, understanding TIs' drivers of success is of great value. This study aims to analyse the most commercially successful European TIs to identify common drivers and best practices. The analysis focuses on drivers associated with customers, commercial staff, research strategy, S&T Policies, impact, and external factors. Some key drivers and best practices identified are: the inclusion of future needs of industry in research strategy; commercialization as a corporate-level activity, and specialized management.